543 Relationship between shift work and the onset of rheumatoid arthritis; results from the swedish eira case-control study. (24th April 2018) - Lars, Alfredsson; Hedström, AK; Åkerstedt, T; Klareskog, L
Abstract : Introduction: Shift work has previously been associated with increased RA risk in females. The aim of this study was to investigate the potential association between permanent night shift work, rotating shift work, and day oriented shift work, and risk of developing anti- citrullinated peptide antibodies (ACPA) positive and ACPA negative RA. Methods: The present report is based on a Swedish population-based, case-control study with incident cases of RA (1951 cases, 2225 matched controls). Using logistic regression, occurrence of RA among subjects who have been exposed to different kinds of shift work was compared with that among those who have never been exposed, by calculating the odds ratio (OR) with a 95% confidence interval (CI). Result: Rotating shift work and day oriented shift work were associated with a 30% increased risk of developing ACPA positive RA, but not ACPA negative RA. There was an inverse association between permanent night shift work and risk of both ACPA positive RA (OR 0.7, 95% CI: 0.6 to 0.9) and APCA negative RA (OR 0.8, 95% CI: 0.6 to 1.0). For both subsets of RA, significant trends showed a lower risk of developing RA with increasing duration of permanent night shift work. Discussion: Sleep restriction as a consequence of shift work is associated with several biological effects among which changes in melatonin production may be involved. The present epidemiological findings of a complex relationship between sleep patterns and different forms of RA may be of importance for increasing the understanding of the pathophysiology of RA.